Spatial diversity of thermal preferences of vascular plants in Łódź - Witosławski, Piotr; Bomanowska, Anna (Biodiversity: Research and Conservation, 2008)
Using temperature indicator values according to Ellenberg, spatial diversity of the vascular flora was determined with regard to thermal preferences of species growing in the area of Łódź (the city with the third largest population in Poland). Study results were compared to meteorological data indicating the presence of an urban heat island (UHI). Analysis of spatial diversity of thermal preferences of the flora was conducted with regard to 292 basic study fields - squares with sides 1 km long. Indicator values of thermal preferences of the flora were determined for the flora of each basic study field - the number and percentage share of thermophilous species (T>6) as well as the average of temperature indicator values. Thermal requirements of the vascular plant species occurring in basic fields within the area of compact tenement-style buildings, industrial and railway terrain are higher than in suburban area. Average temperature indicator values for the flora of basic study fields vary from 5.28 in the peripheries to 5.97 in city centre, while the number of thermophilous species - from 1 to 34, and percentage share of thermophilous species - from 0.6% to 17.5%.